Antibiotic Resistance Patterns of Pseudomonas aeruginosa Bacterial Species Isolated from Various Clinical Samples: Antibiotic Resistance of Pseudomonas aeruginosa - Soomro, Qandeel Abbass; Nabi, Abdul; Tunio, Sarfraz Ali; Qureshi, Abdul Sattar; Brohi, Nazir Ahmed; Khushik, Faryal Ahmed; Dahri, Abdul Sami; Patrick, Asim (Pakistan Journal of Health Sciences, 2024)
Pseudomonas aeruginosa infections have become a real burden in healthcare settings, contributing substantially to nosocomial infections. The emergence of several drug-resistant strains was the major issue causing massive mortality. Multiple-drug resistant Pseudomonas aeruginosa isolates containing beta-lactamase were becoming more prevalent. Objective: To investigate and characterize the antibiotic resistance patterns of Pseudomonas aeruginosa isolated from different clinical samples. Methods: A total of 618 different clinical samples including blood, pus and urine samples were collected from the patients visiting Indus Medical College Hospital Tando Muhammad Khan, Sindh, Pakistan. All the clinical samples were processed for the isolation of bacterial species using specific culture media. The identification of Pseudomonas aeruginosa strains was achieved based on Gram’s staining and certain biochemical tests including Cetrimide test. Moreover, antibiotic susceptibility testing was determined by Kirby-Bauer disc diffusion method. Results: A total of 452 bacterial strains were isolated and pure cultured from different clinical samples. Among these, 60.62% were Gram-negative and 25% of the total isolates were found to be Pseudomonas aeruginosa strains. Antibiotic sensitivity testing results revealed the highest resistance ratio of Pseudomonas aeruginosa strains against Ticarcillin (46.02%), while Colistin showed the lowest resistance (3.54%). Overall, 14.15% of the isolates of Pseudomonas aeruginosa strains were found to be multi-drug-resistant bacteria. Conclusion: The results of the present study reveal an increased ratio of antibiotic resistance particularly of Ticarcillin, piperacillin and imipenem in Pseudomonas aeruginosa isolated from various clinical samples.